Scientific Production of Journals in Heart Transplantation: A Bibliometric Study - MC Lakshminarasimhappa; Kemparaju, T D; Ramesha (International Journal of Knowledge Content Development & Technology, 2025)
Heart transplantation is a surgical treatment that is performed on patients with end-stage heart failure for different causes. Since the increasing number of heart failures and dynamic growth in the research on heart transplantation, bibliometrics was performed to investigate the impact of the most productive journals in this domain. The bibliographical details of 49791 articles were extracted from the Scopus database from 1994 to 2023, which were scattered across 3914 journals. The Journal of Heart and Lung Transplantation secured the top rank, producing 3563 (7.16%) articles, and placed in second position, having 129600 (9.88%). However, the journal Circulation dominated by holding 142717 (10.88%) citations for 983 articles for 30 years. Likewise, the top 30 leading journals covered 43.91% of the total publications. Bradford’s Law examines the research on the ratio of one-third of the total publications into 1: n: n2 (3 zones) and the scattered as 13: 148: 3754, Bradford’s multiplier is 18.37. Initially, the Bradford distribution does not fit with the current data until Leimkuhler’s mathematical model is applied. Finally, it is scrutinised with Leimkuhler’s model, Bradford’s multiplier 2.8494 is validated, and the error percentage is -0.04229.